1991
DOI: 10.1002/tea.3660280604
|View full text |Cite
|
Sign up to set email alerts
|

Testing the ecological validity of teacher‐provided versus student‐generated postquestions in reading college science text

Abstract: This study compared the achievement of high-and low-reading-ability students in two classes of a one-semester introductory college biology course after they either received and used teacher-provided questions posed at various taxonomic levels on textual reading assigned over a five-week period (Group 1) or learned via training to generate and use their own questions at the identical taxonomic levels based on the same text over the same period of time (Group 2). Independent variables included (a) form of questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Koch & Eckstein, 1991;Pearson, 1991). Koch and Eckstein (1991) found that there was improvement in college physics students' reading comprehension of texts when they were taught the skill of formulating questions about textual material.…”
Section: Reading Comprehension Of Science Textsmentioning
confidence: 99%
See 1 more Smart Citation
“…Koch & Eckstein, 1991;Pearson, 1991). Koch and Eckstein (1991) found that there was improvement in college physics students' reading comprehension of texts when they were taught the skill of formulating questions about textual material.…”
Section: Reading Comprehension Of Science Textsmentioning
confidence: 99%
“…Hence, this strategy of formulating questions stimulated students' awareness of their difficulties in reading comprehension and could be used as a self-monitoring technique. One finding that does not fit the general pattern that demonstrates the value of studentgenerated questions comes from the work of Pearson (1991). He compared the achievement of college biology students after they had used either teacher-provided or self-generated questions when reading science texts.…”
Section: Reading Comprehension Of Science Textsmentioning
confidence: 99%